1991
DOI: 10.1111/j.1432-1033.1991.tb16387.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of pancreatic and gastric lipases by tetrahydrolipstatin and alkyl‐dithio‐5‐(2‐nitrobenzoic acid)

Abstract: We studied the covalent inhibition of lipases by the monolayer technique. We report the inactivation of porcine pancreatic and human and rabbit gastric lipases, acting on mixed monomolecular films of dicaprin containing tetrahydrolipstatin or new hydrophobic disulfide compounds, which can be described as a 'poisoned-interface' system.A kinetic model is presented for depicting the covalent inactivation of lipolytic enzymes at a lipid/water interface. The stoichiometry of the interfacial situation can be describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 28 publications
3
42
0
2
Order By: Relevance
“…These data suggest that, despite the importance of a sulphydryl group, these enzymes are probably serine hydrolases. This is supported by the results of Moreau et al (1991), who showed that the essential sulphydryl group and the E600-label1ed serine function independently.…”
Section: Identification Of Catalytic Residuessupporting
confidence: 54%
“…These data suggest that, despite the importance of a sulphydryl group, these enzymes are probably serine hydrolases. This is supported by the results of Moreau et al (1991), who showed that the essential sulphydryl group and the E600-label1ed serine function independently.…”
Section: Identification Of Catalytic Residuessupporting
confidence: 54%
“…Reduction of lipids blood levels observed could be explained by saponins, polyphenols and alkaloids containing in extract. In fact, saponins, polyphenols and alkaloids could form complex with cholesterol and bile acids and cause theirs excretion in feces (Oakenfull and Hood, 1979). Creatinin levels showed no changed in the group fed with HFD + aqueous tuber extract, but it is increased in negative control group which fed with HFD only.…”
Section: Discussionmentioning
confidence: 91%
“…Since food intake is low in rats treated with extracts, the weight loss could be due to the effect of aqueous tuber extract which would reduce appetite. The inhibition of intestinal lipase and absorption of fatty acid by polyphenols could also induce loss of weight as explain by Ransac et al (1991) on their study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to validate a possible application of the PHI-BLA assay in the screening of lipase inhibitors, THL, a well-known covalent inhibitor of digestive lipases ( 56,57 ), was used. Because the inhibition by rHPL and RGL by THL has been extensively studied with other methods (pH-stat technique, monomolecular fi lms), these lipases were chosen for testing the PHIBLA assay.…”
Section: Study Of Lipase Inhibition Using Phiblamentioning
confidence: 99%